Comparison of Heat Transfer Performance of Lattice-Structured Heat Sinks - Christo, Jerome (Indonesian Journal of Computing, Engineering, and Design (IJoCED), 2024)
This paper presents a comparative study of the heat transfer performance of lattice-structured heat sinks. Twenty different unit cells are chosen, and heat sinks are modeled in nTop with constant unit cell size. Al 6061 alloy is chosen as the material for analysis due to its good thermal conductivity, low weight, low cost, and high strength. Steady-state thermal analysis is performed using ANSYS with constant input parameters for all samples. Heat flux and temperature distribution within the heat sinks are analyzed. From the simulation, it was found that TPMS and plate-based heat sinks outperform other types with better heat transfer.